Integrasi Prinsip Green Islamic Economy dalam Pengelolaan Limbah Tahu: Model Sirkular Berbasis Biogas - Nadir, Moh; Umamah, Nur; Fadllan (Lajnah Ta'lif wan Nasyr Nahdlatul Ulama (LTN-NU) Kabupaten Probolinggo, 2025)
The management of tofu wastewater is an ecological issue that often triggers river pollution, unpleasant odors, and a decline in environmental quality. This study was conducted to analyze how a community based waste management model grounded in green islamic economy principles can address these problems while simultaneously generating economic and socio religious benefits for the community in Bicorong Village, Pakong, Pamekasan. The research employed a qualitative approach with a case study design, involving field observations, in depth interviews with tofu industry owners, biogas managers, village officials, and beneficiary communities, as well as document analysis. The data were analyzed thematically to illustrate patterns of innovation adoption, social dynamics, and multidimensional impacts. The findings show that the biogas innovation significantly reduces water pollution, eliminates odor pollution, and produces alternative energy that lowers household expenses and stimulates local economic activities. Additionally, religious values such as maslahah, the prohibition of israf, and the concept of khalifah serve as moral legitimacy that accelerates community acceptance, strengthened by village regulations as institutional instruments. The study concludes that the success of waste management is not only determined by technological effectiveness but also by the integration of religious values, local culture, and institutional structures. This model holds potential as a reference for sustainable environmental development within muslim communities based on green economics and community participation.